1994
DOI: 10.1128/mcb.14.6.3906
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid expression of the heme-regulated eIF-2 alpha kinase.

Abstract: The role of heme-regulated eIF-2a kinase (HRI) in the regulation of protein synthesis in rabbit reticulocytes is well documented. Inhibitors of protein synthesis with properties similar to those of HRI have been described in some nonerythroid cell types, but it has not yet been determined whether these eIF-2o kinase activities are mediated by HRI or one or more as yet uncharacterized kinases. We have studied the expression of mRNA, polypeptide, and kinase activities of HRI in various tissues from both nonanemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 49 publications
1
38
2
Order By: Relevance
“…We have shown previously that HRI is predominantly expressed in the erythroid lineage (29). This is the first demonstration to our knowledge that HRI protein is expressed at a substantial level in nonerythroid cells.…”
Section: Iron Homeostasis and Hepcidin Expression In Hri Deficiencysupporting
confidence: 55%
“…We have shown previously that HRI is predominantly expressed in the erythroid lineage (29). This is the first demonstration to our knowledge that HRI protein is expressed at a substantial level in nonerythroid cells.…”
Section: Iron Homeostasis and Hepcidin Expression In Hri Deficiencysupporting
confidence: 55%
“…However, HRI Ϫ/Ϫ fetal liver cells failed to respond to arsenite despite the response to amino acid and serum starvation. In nonerythroid cells, PKR is likely the eIF2␣ kinase activated by arsenite, since little or no HRI is expressed in nonerythroid cells (13). It has been reported that PKR is activated by arsenite in murine interleukin-3-dependent NFS/N1.H7 cells (21) and NIH 3T3 and MEF cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NOC-9 markedly enhanced Effect of NO on HRI Activity in Non-erythroid Cells-Possible regulatory roles for HRI in nonerythroid cells have yet to be explored in detail. Although HRI expression was previously believed to be specific to erythroid cells (4,38,39), mRNA encoding HRI has been reported to be expressed in several nonerythroid tissues (40,41). A search of the data base of expressed sequence tags, dbEST (Table I) indicated that HRI mRNA is expressed in a wide variety of nonerythroid cells and tissues, as well as a variety of tumors.…”
Section: Regulation Of Hri By No and Comentioning
confidence: 99%